2008
DOI: 10.1016/j.actpsy.2008.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in response selection for pure and mixed stimulus–response mappings and tasks

Abstract: Two experiments examined effects of mixed stimulus-response mappings and tasks for older and younger adults. In Experiment 1, participants performed two-choice spatial reaction tasks with blocks of pure and mixed compatible and incompatible mappings. In Experiment 2, a compatible or incompatible mapping was mixed with a Simon task for which the mapping of stimulus color to location was relevant and stimulus location irrelevant. In both experiments older adults showed larger mixing costs than younger adults and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 34 publications
3
26
3
Order By: Relevance
“…An ANOVA was conducted on the RTs for the task repeat trials only, with mixing condition as a between-subjects factor (three levels), and blocks (eight), SE (two), and preceding congruency (two) as withinsubjects factors. The SE was clearly significant [F(1,43) It is remarkable that, also here, the SE did not reverse in the incompatible condition, which is in contrast to most other similar studies Vu & Proctor, 2008).…”
Section: Methodscontrasting
confidence: 54%
See 2 more Smart Citations
“…An ANOVA was conducted on the RTs for the task repeat trials only, with mixing condition as a between-subjects factor (three levels), and blocks (eight), SE (two), and preceding congruency (two) as withinsubjects factors. The SE was clearly significant [F(1,43) It is remarkable that, also here, the SE did not reverse in the incompatible condition, which is in contrast to most other similar studies Vu & Proctor, 2008).…”
Section: Methodscontrasting
confidence: 54%
“…This was not the case in the present study, where we found an overall decrease of the SE only in the mixed incompatible condition. The difference between their results and ours cannot be explained by a frequency effect (50% location-relevant trials in , as compared with only 33% in the present setup), because a strong reversal was also found by Vu and Proctor (2008), where 33% location relevant trials also were used. As was explained before, stimulus eccentricity may be the factor responsible for this difference.…”
Section: Author Notecontrasting
confidence: 49%
See 1 more Smart Citation
“…In Experiment 2, Castel et al also tested Alzheimer's disease (AD) patients, and the results were similar to those for healthy older adults: The Simon effect of mild AD patients increased over time. In contrast to these studies showing a positive slope for older adults' Simon effect functions, for the standard color Simon task, Proctor, Pick, Vu, and Anderson (2005) and Vu and Proctor (2008) found a decrease of the Simon effect across RT bins for healthy older adults that was not significantly different from that for younger adults. These results suggest that the difficulty in ignoring/suppressing activation from irrelevant stimulus location evidenced by older adults in other studies may be a consequence of the relevant stimulus dimension also conveying spatial information.…”
Section: Decreasing Functions For Bimanual Keypresses To Visual Left-mentioning
confidence: 95%
“…For studies in which keypresses were made with the left and right index fingers to lateralized stimuli of one of two colors, the Simon effect has typically been largest at the shortest one or two RT bins and then decreased across the remaining bins, as in De Jong et al's (1994) study (e.g., Kubo-Kawai & Kawai, 2010;Proctor, Yamaguchi, Zhang, & Vu, 2009, location control condition of Experiment 1; Vu & Proctor, 2008, pure Simon effect condition of Experiment 2). For example, in Proctor et al's (2009) study, the Simon effect for the location control condition was approximately 35 ms at the first of 4 RT bins and decreased to slightly less than 0 ms at the longest RT bin.…”
Section: Distributional Analyses Of the Simon Effectmentioning
confidence: 99%